2001
DOI: 10.12968/denu.2001.28.9.464
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion, Orthodontics and Bullying

Abstract: Bullying is endemic among schoolchildren, and the effects can be devastating and long lasting. The persistently bullied child appears to represent a certain psychological type, with poorly developed social skills and a submissive nature. Physical appearance does appear to play a role, which includes facial and dental appearance, although these tend not to be primary factors. Teasing related to dental appearance appears to be particularly hurtful. There is little evidence of a marked increase in self-esteem fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 20 publications
0
42
1
3
Order By: Relevance
“…Within this age range, in the beginning of adolescence, social life becomes more intense and the appearance becomes more important for the young teenagers, and such characteristics are closely related to the emotional wellbeing. It should be considered that certain occlusal conditions, like visible malocclusions, excessive overjet with incomplete lip closure, crowded incisors, and large diastema between incisors, may result in children teasing and bullying (8). This affects their social and emotional well-being, and results in a lower self-esteem (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this age range, in the beginning of adolescence, social life becomes more intense and the appearance becomes more important for the young teenagers, and such characteristics are closely related to the emotional wellbeing. It should be considered that certain occlusal conditions, like visible malocclusions, excessive overjet with incomplete lip closure, crowded incisors, and large diastema between incisors, may result in children teasing and bullying (8). This affects their social and emotional well-being, and results in a lower self-esteem (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that malocclusions are related to the occurrence of bullying, and that the teasing from others due to the teeth appearance influences the self-reported need for orthodontic treatment (8).…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent media coverage including national campaigns and social networking sites within the United Kingdom have focused on the issue and brought it into the public domain. Its extent is further highlighted by the finding that between 1997 and 1998, 17% of all calls received by Childline were related to bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Through a logistic regression analysis it was possible to calculate that people with malocclusion class II and III are more likely to have a negative impact on quality of life than individuals with class I. This was probably due to the fact that individuals with most severe malocclusions are more likely to suffer physical and psychosocial problems [38] such as dental traumas [39] and bullying [40] which directly interfere with the quality of life. A metaanalysis on the social effects of bullying associated with malocclusion suggested that victims suffer from psychological problems [41], and the present study shows that physical pain and psychological discomfort, followed by psychological disability (Figure 03), were the items that caused the greatest negative impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%